One holy man, one eponym, three distinct diseases. St. Anthony’s fire revisited - Cervellin, Gianfranco; Longobardi, Ugo; Lippi, Giuseppe (Acta Biomedica Atenei Parmensis, 2020)
The use of eponyms adds a valuable historical context to the art of medicine, and shall hence be encouraged, nevertheless their use must always reflect an appropriate historical and medical terminology. A bizarre narration concerns the widespread term “St. Anthony’s fire”, which has been used for denoting not less than three distinct diseases. In this article we underscore that at least three distinct diseases, one toxic (i.e., ergotism) and two infectious (i.e., erysipelas and herpes zoster) have been called, in different times and countries, with the same eponym term of “St. Anthony’s fire”, whilst some other diseases may have also been comprised under this “umbrella” definition. It is possible, for example, that even some cases of plague may have been misclassified as “St. Anthony’s fire”. This article also deals with the importance of this topic in the history of art. Several important artists in different periods, in particular painters, were inspired from the history of St. Anthony, who is generally represented in association with fire (representing the burning pain of the diseases), pig (symbolizing the fat of pigs used in the past for relieving skin symptoms), and different “temptations” (devils, food, gold, jewelry, etc.). A literary masterwork is also cited and discussed.